Concepts of Knowledge Management in Library & Information Services at Central Forest Library: A Case study. - Ushakumari, S.; Narasimhaiah, Seebi (Qualitative and Quantitative Methods in Libraries, 2017)
This paper presents a Study on Library and Information services at Karnataka forest department Central Forest Library. The growing need for knowledge management has influenced every component and operation of a library. Knowledge management requires more effective methods of information handling, speedy transfer of information and linking of information with individuals and their activities. It demands library patron centered development of information systems and services. Development of information communication technology (ICT) and its applications in Library and Information Centers, the concept of document management has changed to information management and the entire scenario of information management has started its change to knowledge management.